Increases in c-Yes Expression Level and Activity Promote Motility But Not Proliferation of Human Colorectal Carcinoma Cells - Jane Barraclough; Cassandra Hodgkinson; Alison Hogg; Caroline Dive; Arkadiusz Welman (Neoplasia: An International Journal for Oncology Research, 2007)
Increases in the levels and/or activity of nonreceptor tyrosine kinases c-Src and c-Yes are often associated with colorectal carcinogenesis. The physiological consequences of increased c-Yes activity during the early and late stages of tumorigenesis, in addition to the degree of redundancy between c-Yes and c-Src in colorectal cancer cells, remain elusive. To study the consequences of increases in c-Yes levels and activity in later stages of colorectal carcinogenesis, we developed human colorectal cancer cell lines in which c-Yes levels and activity can be inducibly increased by a tightly controlled expression of wild-type c-Yes or by constitutively active mutants of c-Yes, c-YesY537F, c-YesΔr6aa. c-Yes induction resulted in increased cell motility but did not promote proliferation either in vitro or in vivo. These results suggest that in later stages of colorectal carcinogenesis, elevations in cYes levels/activity may promote cancer spread and metastasis rather than tumor growth.